Introduction to human factors and ergonomics for engineers - Lehto, Mark (Human factors and ergonomics, 2013)
Emphasizing customer oriented design and operation, Introduction to Human Factors and Ergonomics for Engineers explores the behavioral, physical, and mathematical foundations of the discipline and how to apply them to improve the human, societal, and economic well being of systems and organizations. The book discusses product design, such as tools, machines, or systems as well as the tasks or jobs people perform, and environments in which people live. The authors explore methods of obtaining these objectives, uniquely approaching the topic from an engineering perspective as well as a psychological standpoint.The 22 chapters of this book, coupled with the extensive appendices, provide valuable tools for students and practicing engineers in human centered design and operation of equipment, work place, and organizations in order to optimize performance, satisfaction, and effectiveness. Covering physical and cognitive ergonomics, the book is an excellent source for valuable information on safe, effective, enjoyable, and productive design of products and services that require interaction between humans and the environment.